Effect of Speed Agility Quickness and Circuit Training on Lipid Profile of Soccer Players: An Observational Study - Farooque, Sm; Mitra, Mukesh; Das, Prasanta Kumar (Physical Education Theory and Methodology, 2023)
Study purpose. This observational study aims to investigate the impact of a Speed Agility Quickness (SAQ) and Circuit training program on the lipid profile of soccer players. The study focuses on analyzing changes in high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very-low-density lipoprotein (VLDL) cholesterol concentrations after the intervention. Materials and methods. The study involved a total of 30 elite soccer players with the mean (Sd) of age 16.93 (1.20) years; stature 5.66 (0.16) feet; weight 59.93 (5.47) kg. All the players selected for the study were registered players of Poloi Academy, Imphal, Manipur. The participants were divided into two groups, i.e., the SAQ and Circuit groups, and underwent a 12 weeks SAQ and Circuit training program respectively, which was conducted 3 days per weeks. Blood samples were collected before and after the intervention to measure HDL, LDL, and VLDL cholesterol levels. The participants’ lipid profiles were assessed using standard laboratory techniques. Results. The results of this study demonstrated significant changes in the lipid profiles of the elite soccer players following the SAQ and Circuit training program. The intervention resulted in a significant increase in HDL cholesterol levels. Simultaneously, there was a substantial decrease in LDL and VLDL cholesterol concentrations. Conclusions. The increase in HDL cholesterol and reduction in LDL and VLDL cholesterol levels indicate a potential decrease in the risk of cardiovascular diseases and related health issues. Considering the importance of lipid metabolism in athletic performance and overall well-being, this study provides valuable insights for coaches, athletes, and sports professionals in designing targeted training regimens to optimize cardiovascular health among soccer players. However, further research with larger sample sizes and long-term follow-ups is warranted to validate and generalize these findings across diverse populations and sports disciplines.